Green space and the health of the older adult during pandemics: a narrative review on the experience of COVID-19 - Tabrizi, Nasibeh; Lak, Azadeh; Moussavi.A, S. Mohammad Reza (Frontiers in Public Health, 2023)
Introduction Aging is an inevitable process that leads to changes in various dimensions of older adult life, including physical, psychological, and social aspects. Unfortunately, older adults are more susceptible to health problems caused by adverse experiences such as the Corona outbreak. Aim The current study examines the lived experience of older adults in facing the conditions of the Corona epidemic to see how green spaces at various scales can influence the physical and mental health of this group. Method Relevant articles published, from 2019 to February 17, 2023, were searched using in the Scopus and Web of Science databases. Eligible studies published in English and all studies passed a quality evaluation. Result In the final search, 40 articles were selected and analyzed. The majority of studies conducted during the pandemic categorized the impact of green spaces on the health of older adults into three main categories: Place-based attribute, Process, and Function. Conclusion The findings of this study demonstrated that people were using private green spaces (gardens, balconies, etc.), small local green public spaces, sitting and gathering spaces in the neighborhood, nearby open spaces, and urban green-blue spaces throughout the epidemic era. They visited green spaces outside the city and urban areas, including urban gardens, agricultural areas, forestlands, and pastures. In this research, we investigated the characteristics of these spaces and classified them into four physical categories: urban landscape, land use, activity, movement, and accessibility. The results showed that exposure to nature or green space improved physical and mental health and increased attention and decision-making quality in older people. We have proposed design implications recommendations for crises to improve safety, security, and social capital by increasing the safe access of older adults to diverse and high-quality green spaces on different scales, which will ultimately enhance the physical and mental health of people in different age groups.